Transcranial direct current stimulation combined with language-cognitive training improves language and cognitive ability in children with language delay - Zhou, Huichang; Xu, Yunxian; Chen, Lishan; Yuan, Jiajian; Guan, Zhiyong; Liang, Peng (Frontiers in Neurology, 2024)
Introduction Language delay cannot be ignored, and there is an urgent need to determine therapies that elicit better results in a short period. However, whether transcranial direct current stimulation (tDCS) alone or in combination with other therapies can promote recovery of language and cognitive function in children with language delay remains unknown. This study aims to explore the effects of tDCS combined with language-cognitive training and home-based rehabilitation on language and cognitive ability in children with language delay. Methods Children with language delay who visited the Department of rehabilitation medicine or the pediatric outpatient clinic of the First People’s Hospital of Foshan from January 2019 to December 2021, totaling 190 in number, were included and randomly divided into 4 groups, i.e., the family guidance group, the tDCS group, the language-cognitive training group, and the comprehensive training group. The family guidance group (47 cases) received home training. The tDCS group (46 cases) received home training and tDCS treatment. The language- cognitive training group (49 cases) adopted home training and language-cognitive training. The comprehensive training group (48 cases) took home training, language-cognitive training, and tDCS treatment. All groups received training 5 times a week for 4 weeks. The Sign-significant relations (S-S) test was applied to evaluate the language comprehension, language expression, basic learning ability, and attitude of communication of the children. Results The language-cognitive training group and the comprehensive training group showed improvement after treatment (p < 0.05) regarding basic learning ability. The communication attitude of the four groups improved after intervention (p < 0.05). Particularly, the comprehensive training group had maximum improvement after intervention. No serious adverse reactions such as epilepsy, headache, and behavioral abnormalities were found. Conclusion tDCS combined with language-cognitive training and home training can improve language and cognitive ability in children with language delay.